MnO nanoparticles with potential application in magnetic resonance imaging and drug delivery for myocardial infarction - Zheng Y (Dove Medical Press, 2018)
Yuanyuan Zheng,1 Hong Zhang,2 Yuping Hu,2 Lu Bai,1 Jingyi Xue1 1Department of Pharmacology, School of Basic Medical Sciences, Capital Medical University, Beijing 100069, People’s Republic of China; 2Department of Chemistry and Biology, School of Pharmaceutical Sciences, Capital Medical University, Beijing 100069, People’s Republic of China Background: Myocardial infarction (MI) is a leading cause of death worldwide. Therefore, nanoparticles that applied for specific diagnosis of the infarcted area and/or local myocardial delivery of therapeutic agents, are highly desired. Materials and methods: Herein, we developed the MnO-based nanoparticles, with magnetic resonance (MR) and near-infrared fluorescence imaging modalities as an MR imaging contrast agent and potential drug vehicle for the detection and treatment of MI. The chemophysical characteristics, targeting ability toward infarcted myocardium, biodistribution, and biocompatibility of the MnO-based nanoparticles were studied. Results: It was found that the MnO-based dual-modal nanoparticles possess high r1 relaxivity and induced no notable in vitro or in vivo toxicity. In a rat model of MI, these nanoparticles represent a very promising MR imaging contrast agent for sensitive and specific detection of the infarcted area, more importantly, without cardiotoxicity, the major defect of conventional Mn-based contrasts. Moreover, ex vivo near-infrared fluorescence imaging indicated that the MnO nanoparticles preferentially accumulate in the infarcted myocardium, which makes them an ideal drug vehicle for MI treatment. Conclusion: In summary, the use of these MnO nanoparticles as a T1-weighted MR imaging contrast agent and potential drug vehicle to target the infarcted myocardium may provide new opportunities for accurate detection of myocardial infarct and treatment of ischemic heart diseases. Keywords: Cy5.5 conjugated MnO nanoparticles, Dual-modal nanoprobe, Near-infrared fluorescence imaging, Myocardial ischemia